Comprehensive study of an air bleeding technique on the performance of a proton-exchange membrane fuel cell subjected to CO poisoning - Sung, Lung-Yu; Hwang, Bing-Joe; Hsueh, Kan-Lin; Su, Wei-Nien; Yang, Chang-Chung (Journal of power sources, 2013)
CO poisoning is a major issue for proton-exchange membrane fuel cells (PEMFCs) when reformate gas is used as a fuel, especially at low temperatures (<80 °C). The performance of a PEMFC is investigated when subject to CO poisoning under different operation conditions and a simplified model is hereby proposed. It is found that even when the a CO-tolerant material like platinum–ruthenium (Pt–Ru) is used as the anode catalyst, the cell loses approximately 40% of its current density within 40 min with hydrogen fuel containing 25 ppm CO. By applying 5% air bleeding, the cell output current can be restored to 90% within 10 min, even at high CO concentrations (200 ppm). However, excessive air bleeding (>10% air) also reduces the cell output power. Based on impedance measurements, CO poisoning can strongly increase the charge transfer resistance without affecting the cell internal resistance. The stability test for 300 h using 200 ppm CO and 5% air bleeding shows that the cell power output can remain stable with the overall degradation less than 2%. From the viewpoints of system design and operation, air bleeding offers a stable power output and allows for a simpler, smaller, and cheaper reformer. •This study covers various temperatures, air bleeding, cell voltages, and CO levels.•A 5% air bleeding recovers 90% cell performance, even at 200 ppm CO.•Proposed model well fits to CO poisoning data at various operating conditions.•Cell degradation is less than 2% in a 300-hr, 5% air bleed durability test.